Effects of sewage sludge application on the chemical properties of two tropical soils - Binadam, Aishah Ramadan Mohamed; Jusop, Shamshuddin; Ishak, Che Fauziah; Abdu, Arifin (Malaysian Society of Soil Science, 2015)
Two tropical soils (an Oxisol and an Ultisol) were treated with three rates of sewage sludge (0, 5, and 10%). The results showed that addition of sewage sludge led to increase in pH, cation exchange capacity (CEC), exchangeable bases (K, Ca, and Mg), available phosphorous (available-P), total carbon (TC), total nitrogen (TN) and heavy metals concentration (zinc and copper). All the parameters mentioned were significantly different with the increase in sewage sludge application rates. The highest concentrations of CEC, exchangeable bases (K, Ca and Mg), available-P, TC, TN, total Zn and total Cu were observed in the 10% treatment.